Comparison of the effectiveness of Solution Focus Brief Counseling (SFBC) and reality group counseling to improve self-Efficacy Career - Widigdo, Rudianto Jati; Eddy Wibowo, Mungin; Saraswati, Sinta (Jurnal Bimbingan Konseling, 2023)
Self-efficacy career is a very important component in determining career selection after graduating from vocational school. The purpose of the study was to analyze the comparison of the level of effectiveness of SFBC group counseling and reality in improving self-efficacy career. The research method using experimental research with pretest-posttest control group design involving 14 vocational school students, and divided into 2 groups. Data collection techniques using the career self-efficacy scale developed by researchers. Data analysis was conducted using statistical techniques Wilcoxon and Man Whitney Test. The results obtained there is a change in the average value between pretest and postetst . Effective reality group counseling and SFBC group counseling. Reality counseling and SFBC are effective for improving career self-efficacy. BK teachers are advised to use reality group counseling in improving students ' self-efficacy caree